2013
DOI: 10.1111/1755-5922.12047
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Levosimendan Administration in Takotsubo Cardiomyopathy: A Case Series

Abstract: SUMMARYBackground: Levosimendan is a noncatecholamine inotrope that does not increase oxygen consumption, utilized for the treatment for acute heart failure with left ventricular (LV) systolic dysfunction. Its use in takotsubo cardiomyopathy (TTC), a disease that contraindicates the use of catecholamine inotropes, is not well known. Methods: We prospectively analyzed 13 consecutive patients with TTC, low ejection fraction (EF) (<35%), and additional Mayo Clinic risk factors who were treated with i.v. infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 30 publications
3
81
0
5
Order By: Relevance
“…Overall we identified 14 published articles involving 17 TBI patients with TC [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Among them, 14 were adults, all except two patients presented with loss of consciousness requiring endotracheal intubation and mechanical ventilation for airway protection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall we identified 14 published articles involving 17 TBI patients with TC [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Among them, 14 were adults, all except two patients presented with loss of consciousness requiring endotracheal intubation and mechanical ventilation for airway protection.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely described after severe brain insult like subarachnoid hemorrhage (SAH, 1.2-28 %) [4][5][6]; however, it rarely occurs in patients with intracerebral hemorrhage, ischemic stroke, and traumatic brain injury (TBI) [7]. Here, we report a case of moderate TBI presenting with severe TC and provide a comprehensive review of all reported TBI cases [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Takotsubo kardiyomiyopatisi, belirgin koroner arter stenozu olmamasına rağmen sol ventrikül duvar hareket bozukluğu, EKG değişiklikleri ve miyokard enzimlerinin salınımı ile karakterize bir sendromdur (11). Genellikle duygusal ya da fiziksel stresör bir tetikleyici sonrası ortaya çıkmaktadır (12). Katekolaminler ve stres ilişkili nöropeptidlerin anormal plazma düzeyleri hastaların sadece %75'inde saptanabilir olmasına rağmen kolaylaştırıcı ana faktör olarak düşünülmektedir (12).…”
Section: Subaraknoid Kanamanın Kalbe Etkileriunclassified
“…Genellikle duygusal ya da fiziksel stresör bir tetikleyici sonrası ortaya çıkmaktadır (12). Katekolaminler ve stres ilişkili nöropeptidlerin anormal plazma düzeyleri hastaların sadece %75'inde saptanabilir olmasına rağmen kolaylaştırıcı ana faktör olarak düşünülmektedir (12). Takotsubo kardiyomiyopatisi tipik olarak apikal akinezi ve bazal segment fonksiyonunun korunması şeklinde tanımlanmaktadır.…”
Section: Subaraknoid Kanamanın Kalbe Etkileriunclassified
“…First evidence for the use of levosimendan comes from 4 case reports who developed TS-related cardiogenic shock [11][12][13] or sepsisassociated TS [14]. Further support demonstrating the safety, feasibility and efficacy of levosimendan has been reported in a first prospective pilot study which included 13 consecutive patients with TS and severe ventricle dysfunction [15]. A continuous infusion of levosimendan at a dose of 0.1 µg/kg/min within the first 24-h of hospital admission improved LV ejection fraction (28 ± 5% at admission vs. 51 ± 8% at discharge, p < 0.001).…”
mentioning
confidence: 99%